The Chitinases as Biomarkers for Amyotrophic Lateral Sclerosis: Signals From the CNS and Beyond - Gaur, Nayana; Perner, Caroline; Witte, Otto W.; Grosskreutz, Julian (Frontiers in Neurology, 2020)
Amyotrophic Lateral Sclerosis (ALS) is a late-onset neurodegenerative condition characterized by the selective vulnerability of motor neurons and the poor life expectancy of afflicted patients. Limited disease-modifying therapies currently exist, which only further attests to the substantial heterogeneity associated with this disease. In addition to established prognostic factors like genetic background, site-of-onset-, and age-at-onset, wide consensus on the role of neuroinflammation as a disease exacerbator and driver has been established. In lieu of this, the emerging literature on chitinases in ALS is particularly intriguing. Individual groups have reported substantially elevated chitotriosidase (CHIT1), chitinase-3-like-1 (CHI3L1), and chitinase-3-like-2 (CHI3L2) levels in the cerebrospinal fluid, motor cortex and spinal cord of ALS patients with multiple and often conflicting lines of evidence hinting at possible links to disease severity and progression. This mini-review, while not exhaustive, will aim to discuss current evidence on the involvement of key chitinases in ALS within the wider framework of other neurodegenerative conditions. Implications for understanding disease etiology, developing immunomodulatory therapies and biomarkers, and other translational opportunities will be considered.